Low-tech print : contemporary hand-made printing - Williamson, Caspar (London : Laurence King Publishing, 2013)
Offers an exploration of hand-made printmaking techniques and how they are used in contemporary design and illustration. This title examines the resurgence in the popularity of printmaking, with chapters on screenprinting, letterpress, relief printing and other printing methods.
boek